Media studies texts, production, context - Long, Paul 1967-; Johnson, Beth; MacDonald, Shana; Bader, Schem Rogerson; Wall, Tim; Bakir, Vian; McStay, Andrew (Routledge, an imprint of the Taylor & Francis Group, 2022)
"This thoroughly revised and updated third edition provides a comprehensive introduction to the various approaches to the field, explaining why media messages matter, how media businesses prosper and why media is integral to defining contemporary life. The text is divided into three parts - Media Texts and Meanings; Producing Media; and Media and Social Contexts - exploring the ways in which various media forms make meaning; are produced and regulated; and how society, culture and history are defined by such forms. Encouraging students to actively engage in media research and analysis, each chapter seeks to guide readers through key questions and ideas in order to empower them to develop their own scholarship, expertise and investigations of the media worlds in which we live. Fully updated to reflect the contemporary media environment, the third edition includes new case studies covering topics such as Brexit, podcasts, Love Island, Captain Marvel, Black Lives Matter, Netflix, data politics, the Kardashians, President Trump, 'fake news', the post-Covid world and perspectives on global media forms. This is an essential introduction for undergraduate and postgraduate students of media studies, cultural studies, communication studies, film studies, the sociology of the media and popular culture."--Provided by publisher.